Assessment of the human cutaneous microvasculature using optical coherence tomography: Proving Harvey's proof. (22nd October 2019) - Argarini, Raden; McLaughlin, Robert A.; Naylor, Louise H.; Carter, Howard H.; Green, Daniel J.
Abstract: William Harvey proved the circulation of blood 400 years ago using a combination of ligature application and astute observation that presaged the existence of capillaries. Here we report findings, based on our development of a novel application of optical coherence tomography (OCT), that directly confirm the impact of cuff inflation on microvessels as small as ~30µm. By emulating Harvey's proofs, using cuff inflation at low pressure in the presence and absence of skin heating, we have imaged and quantified significant effects on microvascular diameter and density in humans in vivo. The application of cuff pressure significantly increased microvascular diameter (40.5 ± 4.6 vs 47.1 ± 3.9 µm, P  = .01) and density (8.33 ± 4.3 vs 15.1 ± 4.9%, P <  .01). These impacts were reversed by cuff deflation. Our study also showed the profound impacts of skin heating on microvessel diameter (46.7 ± 5.8 vs 70.6 ± 7.8 µm, P  < .01) and density (14.2 ± 6.5 vs 43.2 ± 9%, P  < .01) in vivo, which were further exacerbated by cuff inflation . Our approach to the direct visualization of the human skin microvasculature is non‐invasive, safe, and easily applied. Future experiments might be directed at questions of microvascular physiology and pathophysiology, such as how different mammals thermoregulate and what impacts cardiovascular disease and diabetes have on microvascular structure and function.